Directing Surface Functions by Inducing Ordered and Irregular Morphologies at Single and Two‐Tiered Length Scales. Issue 2 (23rd February 2021) - Jambor, Michal; Kajánek, Daniel; Fintová, Stanislava; Bronček, Jozef; Hadzima, Branislav; Guagliano, Mario; Bagherifard, Sara
Abstract : A series of simple and scalable surface treatments are used to generate single scale and two‐tiered surface morphologies on metallic surfaces, as described in the article, number 2001057, by Sara Bagherifard and co‐workers. The distinctive and complementary role of micro and nano features, the effect of regularity or orderedness, and the extent of hierarchy are assessed on modulating multiple interface functions.